THE ROLE OF METHODOLGY IN PEDAGOGICAL RESEARCH IN TERMS OF IMPROVING SKILLS OF HIGH SCHOOL STUDENTS PROGRAMMING - Juraković, Linda; Vekić, Marina; Marković, Monika (Journal of international legal communication, 2021)
This paper presents analysis of learning and programming skills of students in High School, course computer technician. Students from all grades participated in the research. In this research the attitudes of students were examined for subject “Algorithms and programming”. Also, research includes programming skills that were tested using specific test. Based on the obtained data, detailed analysis was performed. This analysis includes comparison of programming skills and knowledge between grades in school, comparison of attitudes related to subject and comparison of student’s average grade with results on the given test. Based on the results obtained, proposals for improving the skills of programming are given.